EVALUATION OF FURNACE-02 EFFICIENCY USING THE HEAT LOSS METHOD IN REFINERY UNITS AT PUSAT PENGEMBANGAN SUMBER DAYA MANUSIA MINYAK DAN GAS BUMI CEPU - JAVA - Aliyah Shahab; Achmad Faisal F (Bajang Institute, 2023)
The production or processing of crude oil at PPSDM Migas Cepu using an atmospheric distillation system, which is a method of separating petroleum fractions based on differences in the boiling points of each fraction under atmospheric conditions. Oil processing at PPSDM Migas Cepu first raises the temperature by using a Heat Exchanger and Furnace to obtain the desired feed temperature or temperature. Furnace is heating equipment for processing petroleum which requires the largest operational costs in its processing business. Furnace-02 at the Refinery Unit at PPSDM Migas Cepu is more than 100 years old, and is still operating today. In petroleum processing, the furnace is very important because the furnace is a heat exchanger, which functions to raise the temperature of the petroleum before it is separated in the fractionation column. This study aims to evaluate the efficiency value of furnace-02 from calculations using the heat loss method. Furnace efficiency calculations must be carried out periodically in order to determine furnace performance so as to avoid long-term damage that can lead to maintenance. If the feed that enters the furnace is not in accordance with the specifications, it can burden the furnace's performance. From the results of calculations using the heat loss method, the performance of the furnace-02 at PPSDM Migas Cepu is 86.16%.